Implementation Analysis of Hazard Analysis and Critical Control Points in the Traditional food “Pudak Barokah” at Small Medium Enterprise in Gresik, Indonesia - Sekar Ayu Larasati; Fahimatul Ulum; Erwan Adi Saputro; Anugerah Dany Priyanto; Andre Yusuf Trisna Putra (Nusantara Science and Technology Proceedings, 2022)
Gresik is one of the several centers of the snacks industry. In order to assure food quality and safety, analysis is required to address hazards during the production process. Pudak were made by heating coconut milk, then combined with flour, rice flour, sugar, salt, water, and pandan suji leaves. Pour heated coconut milk over the top, whisked until it is smooth and with no lumps, add cooled coconut milk and vanilla, cover the mixture in leaf wrap, and steam for one hour before serving. This study was carried out to identify and minimize hazards during the production process of pudaks (one of traditional food) and provide recommendations for establishing the Hazard Analysis Critical Control Point (HACCP) system. During the production process, there are three different kinds of possible hazards: biological, physical, and chemical. The Critical Control Point (CCP) might be acknowledged, allowing for a comprehensive implementation of the HACCP. In this publication, the dangers of CCP were analyzed along with suggestions for reducing them.